Motywy i ograniczenia aktywności fizycznej w grupie zawodowej pracowników biurowych = Motives and limitations of physical activity in the professional group of office workers - Kowalczyk, Anna; Kozłowska, Ewelina (Journal of Education, Health and Sport, 2015)
Kowalczyk Anna, Kozłowska Ewelina. Motywy i ograniczenia aktywności fizycznej w grupie zawodowej pracowników biurowych = Motives and limitations of physical activity in the professional group of office workers. Journal of Education, Health and Sport. 2015;5(9):413-428. ISSN 2391-8306. DOI10.5281/zenodo.31014 http://dx.doi.org/10.5281/zenodo.31014 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A413-428 https://pbn.nauka.gov.pl/works/626342 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 15.09.2015. Motywy i ograniczenia aktywności fizycznej w grupie zawodowej pracowników biurowych Motives and limitations of physical activity in the professional group of office workers Anna Kowalczyk1, Ewelina Kozłowska2 1. Studenckie Koło Naukowe przy Katedrze Onkologii i Środowiskowej Opieki Zdrowotnej, Uniwersytet Medyczny w Lublinie 2. Samodzielna Pracownia Epidemiologii, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Autor do korespondencji / Author for correspondence lic. Anna Kowalczyk e-mail: annakowalczyklublin@gmail.com Streszczenie Wprowadzenie i cel pracy. Praca ma na celu określenie czynników wspierających oraz ograniczających podejmowanie aktywności fizycznej w grupie zawodowej pracowników biurowych, w zależności od cech socjodemograficznych uczestników badania. Materiał i metoda. Grupę badaną stanowiło 937 pracowników zatrudnionych w biurach na terenie województwa lubelskiego. Zastosowaną w pracy metodą badawczą był sondaż diagnostyczny, zaś narzędziem badawczym autorski kwestionariusz ankiety składający się z 19 pytań. Analizę statystyczną przeprowadzono za pomocą programu Statistica 10.0. Wyniki. Mieszkańcy miast ponad półtora razy częściej od mieszkańców wsi skłonni są do podjęcia aktywności fizycznej w celu wyrzeźbienia sylwetki (OR=1,80; CI=1,05-3,06), na skutek odczuwanej przyjemności płynącej z aktywności fizycznej (OR=1,88; CI=1,22-2,90) oraz w wyniku przeświadczenia o prewencyjnym działaniu aktywności ruchowej na wiele schorzeń (OR=1,65; CI=1,02-2,67). Natomiast pojawienie się dziecka w rodzinie zwiększa ponad 2,6 razy prawdopodobieństwo, iż aktywność ta będzie utrudniona z powodu braku czasu (OR=2,64; CI=1,91-3,65). Matki i ojcowie rzadziej wskazują jednak na występowanie problemów zdrowotnych (OR=0,59; CI=0,36-0,96) oraz na brak mobilizacji, lenistwo (OR=0,61; CI=0,46-0,81) jako czynników ograniczających aktywność ruchową. Wnioski. Badani pracownicy biurowi podejmując aktywność fizyczną kierują się chęcią zrzucenia lub utrzymania prawidłowej masy ciała, potrzebą dbałości o zdrowie oraz możliwością odreagowania codziennego napięcia i stresu. Czynnikami najbardziej ograniczającymi aktywność fizyczną badanych pracowników są: brak czasu, uczucie zmęczenia oraz brak mobilizacji i lenistwo. Słowa kluczowe: pracownicy biurowi, aktywność fizyczna, rekreacja, motywy, ograniczenia. Summary Introduction and work aim. An aim of the work is to identify factors which support and limit physical activity in the professional group of office workers, depending on sociodemographic features of the study participants. Results. Residents of cities 1.5 times often than country dwellers are willing to undertake physical activity in order to shape their figures (OR = 1.80; CI = 1.05-3.06), as a result of pleasure from the physical activity (OR = 1.88; CI = 1.22-2.90), and as a result of conviction about preventive effect of the physical activity in many diseases (OR = 1.65; CI = 1.02-2.67). However, appearance of a child in the family increases more than 2.6 times probability that this activity will be hindered due to lack of time (OR = 2.64; CI = 1.91-3.65). Mothers and fathers more rarely point to health problems (OR = 0.59; CI = 0.36-0.96) and lack of mobilization, laziness (OR = 0.61; CI = 0.46-0.81) as limiting factors of the physical activity. Conclusions. Examined office workers undertaking the physical activity are guided by desire to lose or keep correct body weight, a need of health care and possibility to relax from daily tension and stress. Factors, which most limit the physical initiative of examined employees, are: lack of time, tiredness, lack of mobilization and laziness. Keywords: office workers, physical activity, recreation, motives, limitations.